The Teeth in the Nasal Cavity - Serat Rahman; Tanuj Madan; Reshu Jindal; Sunil Goyal; Vijay Bhalla; Manikanda Prabhu S (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: Ectopic and supernumerary teeth are sparsely reported. Among the various reported sites, nasal cavity affection is even rarer. This results in easy overlook of such cases.  However, it is pertinent to be aware of this entity as it can lead to considerable morbidity which gets relieved only with correct surgery. These patients may get tentatively diagnosed as chronic sinusitis and get wrongly treated with intranasal corticosteroids, systemic antihistaminics and antibiotics. Owing to its rarity and available literature tending to be in the form of case reports and small case series, every such case must be reported so as to create awareness about it and to facilitate a valid statistical analysis.